Radiation refrigeration fabric and preparation method thereof
By coating Ag-TiO2@BaSO4 on the surface of the fabric, the synergistic effect is used to solve the problem that existing fabrics are difficult to cool in high temperature scenarios, and efficient radiation refrigeration effect is achieved.
Patent Information
- Application Number
- CN202411537135.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Existing cooling fabrics are difficult to achieve effective cooling in high temperature scenarios, and there is a lack of efficient temperature regulation mechanism.
By coating Ag-TiO2@BaSO4 on the surface of the fabric, the radiation refrigeration function is achieved by using the synergistic effect of the hollow core layer of BaSO4, the shell layer of TiO2 and the inlaid nanoAg particles.
This fabric achieves efficient radiation refrigeration effect by enhancing the scattering and infrared emission of sunlight, which is suitable for application in various environments.
Smart Images

Figure BDA0005111838190000081 
Figure BDA0005111838190000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of functional fabrics, and in particular to a radiation cooling fabric and a preparation method thereof. Background Art
[0002] Under the sun, objects will accumulate a lot of heat, causing the surface and internal temperature to rise, which brings many inconveniences and hazards to people's activities. Radiative cooling technology transfers the heat from the heat source through the atmospheric window to the cold source in outer space through infrared radiation, thereby suppressing the rise in the coating surface temperature and reducing the internal temperature of the coating, providing users with a comfortable working and living environment. However, due to the lack of efficient temperature control mechanism, ordinary fabrics are difficult to cope with the drastic changes in ambient temperature. In particular, how to achieve effective cooling in high temperature scenes is a difficult problem that cooling fabrics need to solve urgently. From the existing work, the current cooling fabrics are mainly developed from three ways: convection, conduction, and wet evaporation. For example, heat-conductive materials such as carbon nanotubes, graphene, boron nitride, etc. are used as coatings or embedded in fiber structures to prepare heat-conductive and cool textiles; design fiber cross-sectional structures or use fabric finishing methods to increase the moisture absorption and water conduction rate of fabrics to accelerate the evaporation of human sweat to achieve heat dissipation effect. In addition, other technologies such as adding phase change materials to coatings or fiber structures can use the characteristics of phase change materials to absorb and store human heat to achieve cooling; active cooling clothing with air and liquid cooling systems are also used for human thermal management. In recent years, passive cooling fabrics based on radiant heat regulation have attracted widespread attention because they do not consume any energy. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide a radiant cooling fabric, wherein the surface of the fabric is coated with Ag-TiO 2 @BaSO 4 To achieve the purpose of refrigeration, Ag-TiO 2 @BaSO 4 China-Israel BaSO 4 Hollow core layer, TiO 2 As the shell layer, nano-Ag particles are embedded in TiO 2 Through the synergistic effect of the three, the radiation cooling function is realized.
[0004] Technical solution: A radiant cooling fabric, the fabric comprising a fabric layer and a coating layer, the coating layer is composed of waterborne polyurethane and Ag-TiO 2 @BaSO 4 The Ag-TiO 2 @BaSO 4 China-Israel BaSO 4 Hollow core layer, TiO2 As the shell layer, nano-Ag particles are embedded in TiO 2 superior. The preparation method of the above-mentioned radiation cooling fabric comprises the following steps: S1. Performing hydrophilic treatment on the surface of a fabric to obtain a fabric layer; S2. Ag-TiO 2 @BaSO 4 Add to waterborne polyurethane and stir at 800-1000r / min for 10-30min to make Ag-TiO 2 @BaSO 4 The mixture is evenly mixed with water-based polyurethane, coated on the hydrophilic treated fabric layer, and then pre-baked at 100-110°C for 1-3 minutes and baked at 130-155°C for 2-5 minutes to obtain the radiation cooling fabric. Preferably, the fabric is any one of natural fiber cotton, synthetic fiber fabric or regenerated fiber fabric. Preferably, the Ag-TiO 2 @BaSO 4 The content in waterborne polyurethane is 5-8wt%. Preferably, the Ag-TiO 2 @BaSO 4 The preparation method comprises the following steps: S11. After ball-milling the calcium carbonate, adding it to water, and ultrasonically dispersing it uniformly to obtain a calcium carbonate suspension; S12. Add barium chloride to an aqueous solution of disodium ethylenediaminetetraacetic acid in ammonia, mix and stir evenly, adjust the pH value to neutral, then drop the solution into the calcium carbonate suspension prepared in step S11, stir and mix evenly, drop an aqueous solution of sodium sulfate, stir to react, deposit barium sulfate on the surface of the calcium carbonate, dry and heat treat, add a dilute hydrochloric acid solution after the heat treatment is completed, remove the decomposed calcium oxide, deposit and dry again, and obtain hollow barium sulfate; S13. Take the hollow barium sulfate and ultrasonically disperse it in anhydrous ethanol, add ammonia water, and then add tetrabutyl titanate, keep it warm in a water bath and continue stirring, centrifuge, wash and dry to obtain TiO 2 @BaSO 4 ; S14. The silver nitrate solution and the tannic acid solution were mixed and stirred, and then the sodium borohydride solution was rapidly added dropwise under vigorous stirring to obtain a nanosilver sol; S15. TiO 2 @BaSO 4First, add it to the nano silver sol and stir it evenly, then add the ethanol solution of tetrabutyl titanate to the nano silver sol, then add nitric acid, stir to react, and then age at room temperature, then react the obtained powder at high temperature under nitrogen protection to finally obtain Ag-TiO 2 @BaSO 4 . Preferably, the concentration of the calcium carbonate suspension in step S11 is 2-6 wt %. Preferably, in step S12, the molar ratio of barium chloride, sodium sulfate and calcium carbonate is 10:10:0.5-2, the heat treatment temperature is 800-1000° C., and the time is 0.5-1.5 h. Preferably, in step S13, the mass volume ratio of hollow barium sulfate, ammonia water and tetrabutyl titanate is 0.2-0.4 g: 0.1-0.3 mL: 0.3-0.5 mL, the concentration of hollow barium sulfate in ethanol is 3-5 wt %, the water bath temperature is 40-45° C., and the stirring time is 10-15 h. Preferably, in step S14, the molar ratio of silver nitrate, tannic acid and sodium borohydride is 20-30:4-6:1-3. Preferably, in step S15, the stirring temperature is 60-75°C and the time is 3-5h; the room temperature aging time is 40-60h; the high temperature reaction temperature is 500-600°C and the time is 2-4h. Beneficial effects: The radiant cooling fabric of the present invention has the following advantages: 1. The surface of the finished fabric in the present invention is covered with a layer of hollow coating particles, and these hollow structures can enhance the scattering of sunlight to reduce heat absorption; 2. Titanium dioxide is coated on hollow barium sulfate. The two components are used in combination to combine the advantages of both and achieve a more efficient radiation cooling effect. The scattering effect of titanium dioxide can further reduce the solar energy absorbed by the material, while the high infrared emissivity of barium sulfate ensures that the material can effectively release internal heat into the environment in the form of infrared radiation, which is suitable for application in various environments; 3. The hollow structure in the present invention can provide additional thermal insulation effect, reduce heat transfer inside the material, and further improve the efficiency of radiation cooling. The titanium dioxide coating may be to improve the optical properties of the material, such as enhancing the scattering effect, or to provide better chemical stability and durability. 4. In the present invention, nanosilver particles are embedded in TiO 2 The SPR effect of silver particles can enhance the light absorption of the material in the visible and near-infrared regions, which helps to increase the reflectivity of the material to this part of the solar spectrum, thereby improving the efficiency of radiative cooling. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, and the following embodiments are explanations of the present invention and the present invention is not limited to the following embodiments: Example 1 A method for preparing a radiant cooling fabric, the method comprising the following steps: S1. A surface of the polyester fabric is subjected to a hydrophilic treatment to obtain a fabric layer; S2. Ag-TiO 2 @BaSO 4 Added into waterborne polyurethane, Ag-TiO 2 @BaSO 4 The content of Ag-TiO in waterborne polyurethane was 5wt%, and the mixture was stirred at 800r / min for 30min. 2 @BaSO 4 Evenly mixed with waterborne polyurethane, coated on the hydrophilic treated fabric layer, and then pre-baked at 110℃ for 1min and baked at 155℃ for 2min to obtain radiant cooling fabric; Wherein, the Ag-TiO 2 @BaSO 4 The preparation method comprises the following steps: S11. After ball-milling the calcium carbonate, adding it to water, and ultrasonically dispersing it uniformly to obtain a calcium carbonate suspension having a concentration of 2 wt%; S12. Add barium chloride to an aqueous ammonia solution of disodium ethylenediaminetetraacetic acid, mix and stir evenly, adjust the pH value to neutral, then add the solution dropwise to the calcium carbonate suspension prepared in step S11, stir and mix evenly, add an aqueous sodium sulfate solution dropwise, the molar ratio of barium chloride, sodium sulfate and calcium carbonate is 10:10:0.5, stir to react, deposit barium sulfate on the surface of calcium carbonate, dry and heat treat at a temperature of 1000°C for 0.5h, add a dilute hydrochloric acid solution after the heat treatment is completed, remove the decomposed calcium oxide, deposit and dry again to obtain hollow barium sulfate; S13. Take the hollow barium sulfate and ultrasonically disperse it in anhydrous ethanol. The concentration of the hollow barium sulfate in the ethanol is 5wt%. Ammonia water is added, and then tetrabutyl titanate is added. The mass volume ratio of the hollow barium sulfate, ammonia water and tetrabutyl titanate is 0.2g:0.1mL:0.3mL. Keep warm in a water bath and continue stirring. The water bath temperature is 45°C. The stirring time is 10h. Centrifugal washing and drying are performed to obtain TiO 2 @BaSO 4 ; S14. The silver nitrate solution and the tannic acid solution were mixed and stirred, and then sodium borohydride solution was rapidly added dropwise under vigorous stirring conditions to react, the molar ratio of silver nitrate, tannic acid and sodium borohydride was 20:4:1 to obtain a nanosilver sol; S15. TiO 2 @BaSO4 First, add it to the nano silver sol and stir it evenly, then add the ethanol solution of tetrabutyl titanate to the nano silver sol, and then add nitric acid after the addition is complete. Stir and react at 60 ° C for 5 h, then age at room temperature for 40 h, and then react the obtained powder at high temperature under nitrogen protection at 500 ° C for 4 h to finally obtain Ag-TiO 2 @BaSO 4 . Example 2 A method for preparing a radiant cooling fabric, the method comprising the following steps: S1. A surface of the polyester fabric is subjected to a hydrophilic treatment to obtain a fabric layer; S2. Ag-TiO 2 @BaSO 4 Added into waterborne polyurethane, Ag-TiO 2 @BaSO 4 The content of Ag-TiO in waterborne polyurethane was 8wt%, and the mixture was stirred at 1000r / min for 10min. 2 @BaSO 4 Evenly mixed with waterborne polyurethane, coated on the hydrophilic treated fabric layer, and then pre-baked at 100°C for 3 minutes and baked at 130°C for 5 minutes to obtain radiant cooling fabric; Wherein, the Ag-TiO 2 @BaSO 4 The preparation method comprises the following steps: S11. After ball-milling the calcium carbonate, adding it to water, and ultrasonically dispersing it uniformly to obtain a calcium carbonate suspension having a concentration of 6 wt%; S12. Add barium chloride to an aqueous ammonia solution of disodium ethylenediaminetetraacetic acid, mix and stir evenly, adjust the pH value to neutral, then add the solution dropwise to the calcium carbonate suspension prepared in step S11, stir and mix evenly, add an aqueous sodium sulfate solution dropwise, the molar ratio of barium chloride, sodium sulfate and calcium carbonate is 10:10:2, stir to react, deposit barium sulfate on the surface of calcium carbonate, dry and heat treat at a temperature of 800°C for 1.5 hours, add a dilute hydrochloric acid solution after the heat treatment is completed, remove the decomposed calcium oxide, deposit and dry again to obtain hollow barium sulfate; S13. Take the hollow barium sulfate and ultrasonically disperse it in anhydrous ethanol. The concentration of the hollow barium sulfate in the ethanol is 3wt%. Ammonia water is added, and then tetrabutyl titanate is added. The mass volume ratio of the hollow barium sulfate, ammonia water and tetrabutyl titanate is 0.4g:0.3mL:0.5mL. Keep warm in a water bath and continue stirring. The water bath temperature is 40°C. The stirring time is 15h. Centrifugal washing and drying are performed to obtain TiO 2 @BaSO 4; S14. The silver nitrate solution and the tannic acid solution were mixed and stirred, and then sodium borohydride solution was rapidly added dropwise under vigorous stirring conditions to react, the molar ratio of silver nitrate, tannic acid and sodium borohydride was 30:6:3 to obtain a nanosilver sol; S15. TiO 2 @BaSO 4 First, add it to the nano silver sol and stir it evenly, then add the ethanol solution of tetrabutyl titanate to the nano silver sol, and then add nitric acid after the addition is complete, stir and react, the stirring temperature is 75 ° C, the time is 3 hours, and then age at room temperature, the room temperature aging time is 60 hours, and then the obtained powder is reacted at high temperature under nitrogen protection, the high temperature reaction temperature is 600 ° C, the time is 2 hours, and finally Ag-TiO 2 @BaSO 4 . Example 3 A method for preparing a radiant cooling fabric, the method comprising the following steps: S1. A surface of the polyester fabric is subjected to a hydrophilic treatment to obtain a fabric layer; S2. Ag-TiO 2 @BaSO 4 Added into waterborne polyurethane, Ag-TiO 2 @BaSO 4 The content of Ag-TiO in waterborne polyurethane was 6wt%, and the mixture was stirred at 950r / min for 15min. 2 @BaSO 4 Evenly mixed with waterborne polyurethane, coated on the hydrophilic treated fabric layer, and then pre-baked at 100°C for 3 minutes and baked at 135°C for 4 minutes to obtain radiant cooling fabric; Wherein, the Ag-TiO 2 @BaSO 4 The preparation method comprises the following steps: S11. After ball-milling the calcium carbonate, adding it to water, and ultrasonically dispersing it uniformly to obtain a calcium carbonate suspension having a concentration of 3 wt%; S12. Add barium chloride to an aqueous ammonia solution of disodium ethylenediaminetetraacetic acid, mix and stir evenly, adjust the pH value to neutral, and then drop the solution into the calcium carbonate suspension prepared in step S11, stir and mix evenly, drop sodium sulfate aqueous solution, the molar ratio of barium chloride, sodium sulfate and calcium carbonate is 10:10:0.8, stir to react, deposit barium sulfate on the surface of calcium carbonate, dry and heat treat at a temperature of 950°C for 0.5h, add dilute hydrochloric acid solution after heat treatment, remove the decomposed calcium oxide, deposit and dry again to obtain hollow barium sulfate; S13. Take the hollow barium sulfate and ultrasonically disperse it in anhydrous ethanol. The concentration of the hollow barium sulfate in the ethanol is 3.5wt%. Ammonia water is added, and then tetrabutyl titanate is added. The mass volume ratio of the hollow barium sulfate, ammonia water and tetrabutyl titanate is 0.3g:0.2mL:0.3mL. Keep warm in a water bath and continue stirring. The water bath temperature is 45°C. The stirring time is 10h. Centrifugal washing and drying are performed to obtain TiO 2 @BaSO 4 ; S14. The silver nitrate solution and the tannic acid solution were mixed and stirred, and then sodium borohydride solution was rapidly added dropwise under vigorous stirring conditions to react, the molar ratio of silver nitrate, tannic acid and sodium borohydride was 22:4:1, to obtain a nanosilver sol; S15. TiO 2 @BaSO 4 First, add it to the nano silver sol and stir it evenly, then add the ethanol solution of tetrabutyl titanate to the nano silver sol, and then add nitric acid after the addition is complete, stir and react, the stirring temperature is 65 ° C, the time is 3 hours, and then age at room temperature, the room temperature aging time is 45 hours, and then the obtained powder is reacted at high temperature under nitrogen protection, the temperature of the high temperature reaction is 550 ° C, the time is 4 hours, and finally Ag-TiO 2 @BaSO 4 . Example 4 A method for preparing a radiant cooling fabric, the method comprising the following steps: S1. A surface of the polyester fabric is subjected to a hydrophilic treatment to obtain a fabric layer; S2. Ag-TiO 2 @BaSO 4 Added into waterborne polyurethane, Ag-TiO 2 @BaSO 4 The content of Ag-TiO in waterborne polyurethane was 7wt%, and the mixture was stirred at 850r / min for 25min. 2 @BaSO 4 Evenly mixed with waterborne polyurethane, coated on the hydrophilic treated fabric layer, and then pre-baked at 110°C for 1 minute and baked at 150°C for 3 minutes to obtain radiant cooling fabric; Wherein, the Ag-TiO 2 @BaSO 4 The preparation method comprises the following steps: S11. After ball-milling the calcium carbonate, adding it to water, and ultrasonically dispersing it uniformly to obtain a calcium carbonate suspension having a concentration of 5 wt%; S12. Add barium chloride to an aqueous ammonia solution of disodium ethylenediaminetetraacetic acid, mix and stir evenly, adjust the pH value to neutral, and then drop the solution into the calcium carbonate suspension prepared in step S11, stir and mix evenly, drop sodium sulfate aqueous solution, the molar ratio of barium chloride, sodium sulfate and calcium carbonate is 10:10:1.5, stir to react, deposit barium sulfate on the surface of calcium carbonate, dry and heat treat at a temperature of 850°C for 1.5 hours, add dilute hydrochloric acid solution after heat treatment, remove the decomposed calcium oxide, deposit and dry again to obtain hollow barium sulfate; S13. Take the hollow barium sulfate and ultrasonically disperse it in anhydrous ethanol. The concentration of the hollow barium sulfate in the ethanol is 4.5wt%. Ammonia water is added, and then tetrabutyl titanate is added. The mass volume ratio of the hollow barium sulfate, ammonia water and tetrabutyl titanate is 0.4g:0.3mL:0.5mL. Keep warm in a water bath and continue stirring. The water bath temperature is 40°C. The stirring time is 15h. Centrifugal washing and drying are performed to obtain TiO 2 @BaSO 4 ; S14. The silver nitrate solution and the tannic acid solution were mixed and stirred, and then sodium borohydride solution was rapidly added dropwise under vigorous stirring conditions to react, the molar ratio of silver nitrate, tannic acid and sodium borohydride was 28:6:3, to obtain a nanosilver sol; S15. TiO 2 @BaSO 4 After adding it to the nano silver sol and stirring evenly, the ethanol solution of tetrabutyl titanate was added dropwise to the nano silver sol. After the addition was completed, nitric acid was added dropwise and stirred for reaction. The stirring temperature was 70 ° C for 4 hours. Then, the aging was carried out at room temperature for 55 hours. Then, the obtained powder was subjected to high temperature reaction under nitrogen protection at a temperature of 600 ° C for 4 hours to finally obtain Ag-TiO 2 @BaSO 4 . Example 5 A method for preparing a radiant cooling fabric, the method comprising the following steps: S1. A surface of the polyester fabric is subjected to a hydrophilic treatment to obtain a fabric layer; S2. Ag-TiO 2 @BaSO 4 Added into waterborne polyurethane, Ag-TiO 2 @BaSO 4 The content of Ag-TiO in waterborne polyurethane was 6.6wt% and stirred at 900r / min for 20min. 2 @BaSO 4 Evenly mixed with waterborne polyurethane, coated on the hydrophilic treated fabric layer, and then pre-baked at 105°C for 2 minutes and baked at 140°C for 4 minutes to obtain radiant cooling fabric; Wherein, the Ag-TiO 2 @BaSO 4 The preparation method comprises the following steps: S11. After ball-milling the calcium carbonate, it was added to water and ultrasonically dispersed to obtain a calcium carbonate suspension having a concentration of 5.5 wt%; S12. Add barium chloride to an aqueous ammonia solution of disodium ethylenediaminetetraacetic acid, mix and stir evenly, adjust the pH value to neutral, then drop the solution into the calcium carbonate suspension prepared in step S11, stir and mix evenly, drop sodium sulfate aqueous solution, the molar ratio of barium chloride, sodium sulfate and calcium carbonate is 10:10:1, stir to react, deposit barium sulfate on the surface of calcium carbonate, dry and heat treat at a temperature of 900°C for 1 hour, add dilute hydrochloric acid solution after heat treatment to remove the decomposed calcium oxide, deposit and dry again to obtain hollow barium sulfate; S13. Take the hollow barium sulfate and ultrasonically disperse it in anhydrous ethanol. The concentration of the hollow barium sulfate in the ethanol is 4wt%. Ammonia water is added, and then tetrabutyl titanate is added. The mass volume ratio of the hollow barium sulfate, ammonia water and tetrabutyl titanate is 0.35g:0.25mL:0.4mL. Keep warm in a water bath and continue stirring. The water bath temperature is 40°C. The stirring time is 15h. Centrifugal washing and drying are performed to obtain TiO 2 @BaSO 4 ; S14. The silver nitrate solution and the tannic acid solution were mixed and stirred, and then sodium borohydride solution was rapidly added dropwise under vigorous stirring conditions to react, the molar ratio of silver nitrate, tannic acid and sodium borohydride was 25:5:2 to obtain a nanosilver sol; S15. TiO 2 @BaSO 4 After adding it to the nano silver sol and stirring evenly, the ethanol solution of tetrabutyl titanate was added dropwise to the nano silver sol. After the addition was completed, nitric acid was added dropwise and stirred for reaction. The stirring temperature was 70 ° C for 4 hours. Then, it was aged at room temperature for 40 hours. Then, the obtained powder was reacted at high temperature under nitrogen protection. The temperature of the high temperature reaction was 600 ° C for 4 hours. Finally, Ag-TiO 2 @BaSO 4 . Comparative Example 1 A method for preparing a radiant cooling fabric, the method comprising the following steps: S1. A surface of the polyester fabric is subjected to a hydrophilic treatment to obtain a fabric layer; S2. Ag-TiO 2 @BaSO 4 Added into waterborne polyurethane, Ag-TiO 2 @BaSO 4The content of Ag-TiO in waterborne polyurethane was 6.6wt% and stirred at 900r / min for 20min. 2 @BaSO 4 Evenly mixed with waterborne polyurethane, coated on the hydrophilic treated fabric layer, and then pre-baked at 105°C for 2 minutes and baked at 140°C for 4 minutes to obtain radiant cooling fabric; Wherein, the Ag-TiO 2 @BaSO 4 The preparation method comprises the following steps: S11. After ball-milling the calcium carbonate, it was added to water and ultrasonically dispersed to obtain a calcium carbonate suspension having a concentration of 5.5 wt%; S12. Add barium chloride to an aqueous solution of disodium ethylenediaminetetraacetic acid in ammonia, mix and stir evenly, adjust the pH value to neutral, then drop the solution into the calcium carbonate suspension prepared in step S11, stir and mix evenly, dropwise add an aqueous solution of sodium sulfate, the molar ratio of barium chloride, sodium sulfate and calcium carbonate being 10:10:1, stir to react, deposit barium sulfate on the surface of calcium carbonate, dry, deposit and dry again, and obtain calcium carbonate coated with barium sulfate; S13. The barium sulfate-coated calcium carbonate was ultrasonically dispersed in anhydrous ethanol. The concentration of the barium sulfate-coated calcium carbonate in ethanol was 4 wt%. Ammonia water was added. Then tetrabutyl titanate and hollow barium sulfate were added. The mass volume ratio of ammonia water and tetrabutyl titanate was 0.35 g: 0.25 mL: 0.4 mL. The mixture was kept warm in a water bath and stirred continuously. The water bath temperature was 40 ° C. The stirring time was 15 h. The mixture was centrifuged, washed and dried to obtain TiO 2 @BaSO 4 ; S14. The silver nitrate solution and the tannic acid solution were mixed and stirred, and then the sodium borohydride solution was rapidly added dropwise under vigorous stirring conditions to react, the molar ratio of silver nitrate, tannic acid and sodium borohydride was 25:5:2, to obtain a nanosilver sol; S15. TiO 2 @BaSO 4 After adding it to the nano silver sol and stirring evenly, the ethanol solution of tetrabutyl titanate was added dropwise to the nano silver sol. After the addition was completed, nitric acid was added dropwise and stirred for reaction. The stirring temperature was 70 ° C for 4 hours. Then, it was aged at room temperature for 40 hours. Then, the obtained powder was reacted at high temperature under nitrogen protection. The temperature of the high temperature reaction was 600 ° C for 4 hours. Finally, Ag-TiO 2 @BaSO 4 . Comparative Example 2 A method for preparing a radiant cooling fabric, the method comprising the following steps: S1. A surface of the polyester fabric is subjected to a hydrophilic treatment to obtain a fabric layer; S2. TiO 2 @BaSO 4 Added into waterborne polyurethane, TiO 2 @BaSO 4 The content of TiO in waterborne polyurethane was 8wt%, and the mixture was stirred at 900r / min for 20min. 2 @BaSO 4 Evenly mixed with waterborne polyurethane, coated on the hydrophilic treated fabric layer, and then pre-baked at 105°C for 2 minutes and baked at 140°C for 4 minutes to obtain radiant cooling fabric; Wherein, the TiO 2 @BaSO 4 The preparation method comprises the following steps: S11. After ball-milling the calcium carbonate, it was added to water and ultrasonically dispersed to obtain a calcium carbonate suspension having a concentration of 5.5 wt%; S12. Add barium chloride to an aqueous ammonia solution of disodium ethylenediaminetetraacetic acid, mix and stir evenly, adjust the pH value to neutral, then drop the solution into the calcium carbonate suspension prepared in step S11, stir and mix evenly, drop sodium sulfate aqueous solution, the molar ratio of barium chloride, sodium sulfate and calcium carbonate is 10:10:1, stir to react, deposit barium sulfate on the surface of calcium carbonate, dry and heat treat at a temperature of 900°C for 1 hour, add dilute hydrochloric acid solution after heat treatment to remove the decomposed calcium oxide, deposit and dry again to obtain hollow barium sulfate; S13. Take the hollow barium sulfate and ultrasonically disperse it in anhydrous ethanol. The concentration of the hollow barium sulfate in the ethanol is 4wt%. Ammonia water is added, and then tetrabutyl titanate is added. The mass volume ratio of the hollow barium sulfate, ammonia water and tetrabutyl titanate is 0.35g:0.25mL:0.4mL. Keep warm in a water bath and continue stirring. The water bath temperature is 40°C. The stirring time is 15h. Centrifugal washing and drying are performed to obtain TiO 2 @BaSO 4 . Comparative Example 3 A method for preparing a radiant cooling fabric, the method comprising the following steps: S1. A surface of the polyester fabric is subjected to a hydrophilic treatment to obtain a fabric layer; S2. Ag@BaSO 4 Added into waterborne polyurethane, Ag@BaSO 4 The content of Ag@BaSO in waterborne polyurethane was 6.6wt%, and the mixture was stirred at 900r / min for 20min. 4 Evenly mixed with waterborne polyurethane, coated on the hydrophilic treated fabric layer, and then pre-baked at 105°C for 2 minutes and baked at 140°C for 4 minutes to obtain radiant cooling fabric; Among them, the Ag@BaSO 4 The preparation method comprises the following steps: S11. After ball-milling the calcium carbonate, it was added to water and ultrasonically dispersed to obtain a calcium carbonate suspension having a concentration of 5.5 wt%; S12. Add barium chloride to an aqueous ammonia solution of disodium ethylenediaminetetraacetic acid, mix and stir evenly, adjust the pH value to neutral, then drop the solution into the calcium carbonate suspension prepared in step S11, stir and mix evenly, drop sodium sulfate aqueous solution, the molar ratio of barium chloride, sodium sulfate and calcium carbonate is 10:10:1, stir to react, deposit barium sulfate on the surface of calcium carbonate, dry and heat treat at a temperature of 900°C for 1 hour, add dilute hydrochloric acid solution after heat treatment to remove the decomposed calcium oxide, deposit and dry again to obtain hollow barium sulfate; S13. The silver nitrate solution and the tannic acid solution were mixed and stirred, and then sodium borohydride solution was rapidly added dropwise under vigorous stirring conditions to react, the molar ratio of silver nitrate, tannic acid and sodium borohydride was 25:5:2 to obtain a nanosilver sol; S14. The hollow barium sulfate was first added to the nanosilver sol, stirred evenly and then filtered. The obtained powder was then subjected to high temperature reaction under nitrogen protection at a temperature of 600°C for 4 hours to finally obtain Ag@BaSO 4 . Comparative Example 4 A method for preparing a radiant cooling fabric, the method comprising the following steps: S1. A surface of the polyester fabric is subjected to a hydrophilic treatment to obtain a fabric layer; S2. Ag, TiO 2 ,BaSO 4 Added into waterborne polyurethane, the content of Ag in waterborne polyurethane is 2wt%, TiO 2 The content of BaSO in waterborne polyurethane is 3.5wt%, 4 The content of Ag, TiO in waterborne polyurethane was 3.5wt% and stirred at 900r / min for 20min. 2 and BaSO 4 The mixture is evenly mixed with water-based polyurethane, coated on the hydrophilically treated fabric layer, and then pre-baked at 105°C for 2 minutes and baked at 140°C for 4 minutes to obtain the radiation cooling fabric. Radiative cooling performance: The solar reflectivity and atmospheric window emissivity of polyester fabrics were tested, and the fabric temperature was tested in Wuxi City from 10:00 to 15:00 on May 23, 2024 (the average ambient temperature was 31.5°C). From the above table, we can see that the weight gain of the coated fabric is 50g / m 2 When the solar reflectivity and atmospheric window emissivity of the coated polyester fabric reach 94.2% and 92.9% respectively. The above results show that the radiative cooling coated fabric has a high radiative cooling effect; the average temperature of the fabric and the environment are 26.1℃ and 31.5℃ respectively, and the cooling temperature of the fabric is 5.4℃. Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A radiant cooling fabric, characterized in that: The fabric comprises a fabric layer and a coating layer, wherein the coating layer is composed of waterborne polyurethane and Ag-TiO2@BaSO4, wherein BaSO4 is a hollow core layer, TiO2 is a shell layer, and nano-Ag particles are embedded on TiO2.
2. The method for preparing the radiant cooling fabric according to claim 1, characterized in that: The preparation method comprises the following steps: S1. Performing hydrophilic treatment on the surface of a fabric to obtain a fabric layer; S2. Add Ag-TiO2@BaSO4 to waterborne polyurethane, stir at 800-1000r / min for 10-30min to evenly mix Ag-TiO2@BaSO4 and waterborne polyurethane, apply it on the hydrophilic treated fabric layer, and then pre-bake at 100-110℃ for 1-3min and bake at 130-155℃ for 2-5min to obtain radiant cooling fabric.
3. The method for preparing the radiant cooling fabric according to claim 2, characterized in that The fabric is any one of natural fiber cotton, synthetic fiber fabric or regenerated fiber fabric.
4. The method for preparing the radiant cooling fabric according to claim 2, characterized in that: The content of Ag-TiO2@BaSO4 in waterborne polyurethane is 5-8wt%.
5. The radiant cooling fabric according to claim 1, characterized in that: The preparation method of the Ag-TiO2@BaSO4 comprises the following steps: S11. After ball-milling the calcium carbonate, adding it to water, and ultrasonically dispersing it uniformly to obtain a calcium carbonate suspension; S12. Add barium chloride to an aqueous solution of disodium ethylenediaminetetraacetic acid in ammonia, mix and stir evenly, adjust the pH value to neutral, then drop the solution into the calcium carbonate suspension prepared in step S11, stir and mix evenly, drop an aqueous solution of sodium sulfate, stir to react, deposit barium sulfate on the surface of the calcium carbonate, dry and heat treat, add a dilute hydrochloric acid solution after the heat treatment is completed, remove the decomposed calcium oxide, deposit and dry again, and obtain hollow barium sulfate; S13. Take the hollow barium sulfate and ultrasonically disperse it in anhydrous ethanol, add ammonia water, and then add tetrabutyl titanate, keep it warm in a water bath and continue stirring, centrifuge and wash and dry to obtain TiO2@BaSO4; S14. The silver nitrate solution and the tannic acid solution were mixed and stirred, and then sodium borohydride solution was rapidly added dropwise under vigorous stirring to obtain a nanosilver sol; S15. TiO2@BaSO4 is first added to the nano-silver sol and stirred evenly, and then the ethanol solution of tetrabutyl titanate is added dropwise to the nano-silver sol. After the addition is complete, nitric acid is added dropwise, stirred for reaction, and then aged at room temperature. Subsequently, the obtained powder is reacted at high temperature under nitrogen protection to finally obtain Ag-TiO2@BaSO4.
6. The radiant cooling fabric according to claim 5, characterized in that: The concentration of the calcium carbonate suspension in step S11 is 2-6 wt %.
7. The radiant cooling fabric according to claim 5, characterized in that: In step S12, the molar ratio of barium chloride, sodium sulfate and calcium carbonate is 10:10:0.5-2, the heat treatment temperature is 800-1000° C., and the time is 0.5-1.5 h.
8. The radiant cooling fabric according to claim 5, characterized in that: In step S13, the mass volume ratio of hollow barium sulfate, ammonia water and tetrabutyl titanate is 0.2-0.4 g: 0.1-0.3 mL: 0.3-0.5 mL, the concentration of hollow barium sulfate in ethanol is 3-5 wt %, the water bath temperature is 40-45° C., and the stirring time is 10-15 h.
9. The radiant cooling fabric according to claim 5, characterized in that: In step S14, the molar ratio of silver nitrate, tannic acid and sodium borohydride is 20-30:4-6:1-3.
10. The radiant cooling fabric according to claim 5, characterized in that: In the step S15, the stirring temperature is 60-75° C. and the time is 3-5 h; the room temperature aging time is 40-60 h; the high temperature reaction temperature is 500-600° C. and the time is 2-4 h.
Citation Information
Patent Citations
Energy-consumption-free radiation refrigeration coating as well as preparation method and application thereof
CN116445074A
Double-layer radiation refrigeration coating as well as preparation method and application thereof
CN118638456A
Layered composite anti-radiation fabric and preparation method thereof
CN118664996A